PERTOLONGAN PERTAMA MASYARAKAT AWAM PADA TRAUMA MUSKULOSKELETAL YANG DIAKIBATKAN KECELAKAAN LALU LINTAS - Mahardika, Candra; Abiddin, Andi Hayyun; Mulyadi, Arif (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2026)
Background: In cases of road traffic accidents, musculoskeletal injuries are the most common and are a major contributor to permanent disability. In the field, more than 70% of initial responses to accident victims are performed by bystanders who are first at the scene, yet most of them lack adequate first aid knowledge and skills. This condition often leads to incorrect actions, such as moving victims without immobilization, which worsens injuries and increases the risk of complications and permanent disability Purpose: To determine the level of knowledge and actions of laypersons in providing first aid for musculoskeletal injuries caused by road traffic accidents Methods: This quantitative descriptive study was carried out from February to March 2025 in the Emergency Department of RSUD dr. Soedono Madiun. The sample comprised 30 laypersons who have conducted preliminary management of musculoskeletal trauma, chosen by purposive sampling. Data were gathered utilizing a questionnaire assessing knowledge and actions related to musculoskeletal trauma first aid. Data were examined utilizing frequency and percentage distributions Result: The findings highlight a discrepancy between knowledge and practice, whereby 56.7% of the lay population had adequate knowledge, yet 76.7% exhibited inadequate first aid practices for musculoskeletal trauma Implication: First aid education on musculoskeletal trauma for laypeople provides significant benefits in improving community preparedness and early accident response capabilities. Community-based first aid training is particularly needed for populations in accident-prone areas. In addition, the use of mobile emergency guidance applications may serve as a practical solution to support laypeople in delivering appropriate first aid prior to medical care